Consumption of Cultural Goods in Russia: Scale, Determinants, Differentiation - Rostislav Kapeliushnikov; Natalia Demina (Journal of Economic Sociology, 2021)
This paper is the first in the Russian economic and sociological literature that provides a general stylized picture of the consumption of cultural goods in Russia using microdata from representative household surveys. The empirical basis of analysis is Rosstat’s Complex Observation of the Living Conditions of the Population for 2011–2018, which so far has been ignored by researchers. Four main kinds of cultural goods are distinguished—cinema, theater, concerts and museums—and the probabilities and intensity of their consumption are assessed. The analysis shows that in Russia at present, about every second adult consumes some cultural goods during the year. Cinema is the most popular good, followed by concerts, theater and museums. A regular audience is approximately one-fifth of the total audience. The primary focus of the paper is on evaluating the contributions of various factors of demand for cultural goods. There is also a detailed discussion of another important behavioral question: to what extent does demand by individuals for any one cultural good stimulate their demand for all other ones? In the econometric part of the paper, two types of models are constructed and evaluated: ordinary logit (for likelihood of consumption) and multinomial logit (for intensity of consumption). The results obtained show that two groups of factors make the highest contributions: on the one hand, economic (such as income), and, on the other, cultural (such as education, occupation and experience with the Internet). In the Russian context there is a visible empirical regularity: the higher the income of individuals, the more active they are culturally. The wealthiest groups go to the movies two and a half times more often, to the theaters seven times more often, to concerts twice as often, and to museums six times more often than the poorest ones.